Will diminishing cochlear delay affect speech perception in noise?. (August 2015) - Huang, Ethan I.; Durrant, John D.; Boston, J. Robert
Abstract: Objective: Normal auditory systems appear well habituated to time/phase delays inherent to sound encoding along the hearing organ, sending frequency information non-simultaneously to the central auditory system. Eliminating, or simply perturbing, the cochlear delay might be expected to decrease speech recognition ability, especially under demanding listening conditions. Resources of a larger-scale investigation permitted a preliminary examination of this issue, particularly on a relevant timescale of empirically demonstrated cochlear delays. Design: In a randomized controlled trial study, word recognition was tested for mono-syllabic tokens treated digitally to exacerbate, if not diminish/nullify, such delays. Speech-weighted noise was used to interfere with listening to time-frequency reversed (nominally no delay) versus non-reversed (natural timing) transforms under three treatments of speech tokens: (1) original-digitally recorded; digitally processed to emphasize (2) transient versus (3) quasi-steady-state components. Study sample: Ten normal-hearing young-adult females. Results: The findings failed to demonstrate statistically significant differences between delay conditions for any of the three speech-token treatments. Conclusions: An algorithm putatively diminishing frequency-dependent cochlear delays failed to systematically deteriorate performance in all subjects for the fixed time-frequency transform, stimulus parameters, and test materials employed. Yet, trends were evident such that some effect of perturbing cochlear delays could not be ruled out completely.